Luteolin as a multifaceted immunomodulator: insights into its effects on diverse immune cell populations and therapeutic implications - Wang, Xiaolan; Zhao, Junbo; Li, Ying; Gao, Sujun; Su, Long (Frontiers in Immunology, 2025)
Luteolin, a natural flavonoid, exerts broad immunomodulatory effects across multiple immune cell populations, positioning it as a promising candidate for treating inflammatory diseases, infections, and cancer. This review synthesizes current evidence on luteolin’s effects on T cells, natural killer (NK) cells, dendritic cells (DCs), macrophages, neutrophils, eosinophils, and basophils. Luteolin promotes the differentiation of regulatory T cells (Tregs) and suppresses pro-inflammatory T helper 17 (Th17) and Th2 responses, thereby restoring immune balance in sepsis, allergies, and autoimmunity. In macrophages, it skews polarization toward the anti-inflammatory M2 phenotype via the signal transducer and activator of transcription 3 (STAT3)/STAT6 and peroxisome proliferator-activated receptor γ (PPARγ) pathways, while inhibiting nuclear factor-κB (NF-κB) and NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation. Neutrophil functions are dampened by reduced oxidative stress, adhesion molecule expression, and induction of apoptosis. Luteolin may enhance NK-cell cytotoxicity and DC-mediated antigen presentation while curbing eosinophil and basophil activation in allergic disorders. Despite preclinical successes, future research should prioritize mechanistic insights, structural optimization, and clinical translation to unlock luteolin’s full therapeutic potential.